2022
DOI: 10.30574/gscbps.2022.19.2.0139
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of essential oil from Phoenix dactylifera (L.) seed

Abstract: Oxidative stress has been implicated in the initiation and progression of a plethora of diseases including atherosclerosis, diabetes mellitus, rheumatoid arthritis, neurodegenerative diseases, cardiovascular diseases and cancer. Due to the toxic and mutagenic side effects of some synthetic antioxidant compounds, intense interest is recently converged on natural antioxidants. This study therefore aimed at evaluating the antioxidant potential of essential oil extracted from Phoenix dactylifera seed. Phoenix dact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The effective free radical scavenging effect is also shown by Origanum campactumi, Curcuma zedoaria Rosc, Eucalyptus camaldulensis and Phoenix dactylifera. 49- 51 Ozkan et al 52 worked on Salvia pisidica essential oil and found its better effect on scavenging of free radical and hydroxy radical and inhibition of linoleic acid.…”
Section: Work That Reflect the Antioxidant Activity Of Essential Oilsmentioning
confidence: 99%
“…The effective free radical scavenging effect is also shown by Origanum campactumi, Curcuma zedoaria Rosc, Eucalyptus camaldulensis and Phoenix dactylifera. 49- 51 Ozkan et al 52 worked on Salvia pisidica essential oil and found its better effect on scavenging of free radical and hydroxy radical and inhibition of linoleic acid.…”
Section: Work That Reflect the Antioxidant Activity Of Essential Oilsmentioning
confidence: 99%